2010
DOI: 10.1111/j.1365-2613.2010.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer cell proliferation and angiogenesis in different obese mice models

Abstract: Obesity has been associated with increased incidence and aggressiveness of prostate cancer. Although controversial, several studies suggest that leptin could influence tumour cell growth and proliferation. The main goal of this study was to assess cellular growth of prostate adenocarcinoma cells in obese mice with different endogenous hormonal environments in what relates to leptin circulating levels and sensitivity. Four groups of mice (n = 6/group) were used, namely obese mice with congenital non-functioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 68 publications
(156 reference statements)
4
25
0
Order By: Relevance
“…Our observations were also generally consistent with the results of the studies where RM1 murine prostate cancer cells were injected subcutaneously into the obese ob/ob and db/db mice [8]. Our observations were, however, only partially consistent with the results of the studies where MMTV-Wnt-1 mammary tumors were orthotopically transplanted into the right mammary fat pad of obese ob/ob and db/db mice [9].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our observations were also generally consistent with the results of the studies where RM1 murine prostate cancer cells were injected subcutaneously into the obese ob/ob and db/db mice [8]. Our observations were, however, only partially consistent with the results of the studies where MMTV-Wnt-1 mammary tumors were orthotopically transplanted into the right mammary fat pad of obese ob/ob and db/db mice [9].…”
Section: Discussionsupporting
confidence: 91%
“…These changes were, however, not entirely consistent with the reported risk of developing cancer in homozygous leptin-deficient obese ob/ob mice [8,9]. On the one hand, our observations were generally consistent with the results of the previously reported study where RM1 murine prostate cancer cells were injected subcutaneously into the obese ob/ob mice [8]. This study found positive associations among obesity, cancer and the serum levels of insulin.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations